Pengembangan Instrument Minat Belajar IPA Siswa Sekolah Dasar - Iswanto, Iswanto (Syntax Idea, 2021)
The purpose of the research was to generate an interest in learning science students in grade IV elementary school who met valid and reliable criteria. The variables observed in this study were instruments of interest in learning science with the research subjects of students of SDN Karangrejo 02 and SDN Cingklung in Bancar Subdistrict, Tuban Regency. This research is a type of development research (R&D) by applying plomp research model with five stages including (1) Investigation Phase, (2) Design, (3) Realization, (4) Evaluation and Revision, (5) Implementation. The instruments developed are questionnaires of interest in learning science for elementary school students with indicators of students' feelings of pleasure, interest and attention in learning science. Questionnaire test, conducted grain validation test using correlation technique SPSS application version 23 with the number of question items 20 and respondents (N-24) with a level of significance of 5% (0.05) is 0.404 ( R table). Obtained 13 valid statement items and 7 invalid statement items. Reliability test has Cronbach's Alpha value of more than 60% or 0.6, which is 0.801 which means the poll is said to be Reliable.